PENTINGNYA SIKAP MODERAT PARA DA’I DALAM PERKARA IKHTILAF DI TENGAH MASYARAKAT AWAM - Muhammad Shuhufi; ALMUNAWIR, MUHAMMAD RAHMAN (Sulesana, 2024)
This research aims to analyze the importance of moderate attitudes of preachers in matters of ikhtilaf among ordinary people. A moderate attitude represents a middle path that is neither extreme left nor extreme right. A moderate attitude needs to be instilled by a da’i as a person whose job is to encourage other people to follow and practice Islamic teachings. The main factor in the occurrence of ikhtilaf in society is the difference in the schools/organizations that the preachers follow, giving rise to disputes in society. Every preacher and mass organization will appeal to the school of thought they follow, so that attitudes of putting each other down and criticizing each other become common things found in society. A moderate attitude is one solution in responding to cases of ikhtilaf among ordinary people.